O(s) sentido(s) na prosa breve de Mia Couto e Georgi Gospodinov (Philology, 2022)
The African literature, even more in its Portuguese expression, occupies the space of the exotic extreme in the literary life of Bulgaria, both in terms of interest of ordinary readers and scientific approaches. Nevertheless, four of the masterpieces of the most notorious voices in the contemporary literature in Lusophone Africa have already been translated into Bulgarian. The present text starts from the spontaneous expectations about the strangeness of the African literature of Portuguese expression in the Bulgarian cultural context to present a small comparative study of two works of the short prose of the Mozambican Mia Couto and the Bulgarian Georgi Gospodinov. The comparison seeks to identify multiple points of proximity in the Mozambican and Bulgarian imaginary, focusing on the short stories The girl who did not speak and The blind Vaisha, respectively. The analysis focuses in particular on the topic of the use and interpretation of the human senses, pursuing the final goal of drawing conclusions regarding the proceedings by which the overall meaning of the literary text is constructed by the two authors.
Keywords: Lusophone African literature; contemporary Bulgarian literature; tale; construction; senses